Les jardins partagés franciliens, scènes de participation citoyenne ? - Kaduna-Eve Demailly (EchoGéo)
Since the early 2000’s, community gardens have been multiplied in Île-de-France, supported by City councils. As vicinity gardens managed by inhabitants who are part of a private association, they tend to promote urban vegetation, social cohesion and civic participation. This paper, which focuses on community gardens established on vacant lands, aims at examining several meanings of the concept of participation in order to assess the actual inhabitants’ role. As I will argue, users’ participation is finally restricted to garden’s management and organisation.